2021
DOI: 10.1177/2325967120988798
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Radiographic Outcomes of Intraoperatively Decreasing the Coracoclavicular Distance to 50% of the Unaffected Side in Stabilization of Acute Acromioclavicular Joint Injury: A Retrospective Evaluation

Abstract: Background: The postoperative failure rate of acromioclavicular (AC) joint fixation using the coracoclavicular (CC) stabilization technique is high. Studies have reported that compared with normal intraoperative anatomic reduction, intraoperative overreduction of the AC joint is more successful in achieving a satisfactory anatomic radiographic outcome at 1- to 2-year follow-up. Purpose: To evaluate the functional and radiographic outcomes and complications in patients with acute AC joint injury who underwent c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In CC stabilization and AC capsule repair, a number of studies have reported high incidences of superior displacement or loss of reduction after surgery of 5% to 50%. 4 , 5 , 12 , 18 , 23 The direction of the sutures is one of the important factors that affects postoperative reduction alignment. Seo et al 21 studied the outcomes of single-tunnel CC fixation and reported that an oblique suture direction was related to loss of reduction after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In CC stabilization and AC capsule repair, a number of studies have reported high incidences of superior displacement or loss of reduction after surgery of 5% to 50%. 4 , 5 , 12 , 18 , 23 The direction of the sutures is one of the important factors that affects postoperative reduction alignment. Seo et al 21 studied the outcomes of single-tunnel CC fixation and reported that an oblique suture direction was related to loss of reduction after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an anteroposterior (AP) view of the clavicle was performed preoperatively and postoperatively to identify the distal clavicle fracture or the reduction (Figure 2). The coracoclavicular (CC) distance was defined as the shortest distance between the superior cortex of the coracoid process and the clavicle's undersurface on the clavicle's AP view 23 . The fragment size was defined by the distance between the medial border of the fracture line and the distal border of the clavicle 24 …”
Section: Methodsmentioning
confidence: 99%
“…The coracoclavicular (CC) distance was defined as the shortest distance between the superior cortex of the coracoid process and the clavicle's undersurface on the clavicle's AP view. 23 The fragment size was defined by the distance between the medial border of the fracture line and the distal border of the clavicle. 24 …”
Section: Methodsmentioning
confidence: 99%
“…In this type of case, we prefer to do an overreduction. 6 The AC capsule is repaired using two 2.8-mm metal suture anchors (Arthrex) ( Fig 7 ). The deltotrapezial fascia and deltoid fascia are repaired using VICRYL 3-0.…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%